A new genus and species of Sophiini Townsend, 1936 (Diptera: Tachinidae) from Brazil, with an updated key to the genera of the tribe - de Santis, Marcelo Domingos (Zootaxa, 2018)
Sophiini is a New World tribe of Tachinidae composed, prior to this study, of 19 species in eight genera. Cryptosophia aurulenta gen. and sp. nov. from Amazonas, Brazil, is described and assigned to that tribe. The new genus can be easily distinguished from the other genera in the tribe, mainly by: head with occiput clearly swollen medially; thorax without a proepisternal seta; and meron with pale yellow setae almost indistinguishable from the yellow integument. It is most similar to members of the genera Neosophia Guimarães and Sophiella Guimarães. An updated and illustrated key to the genera of Sophiini is provided, including Cryptosophia gen. nov. Descriptions and illustrations of the female terminalia, spermatheca, and first instar larva are also provided for the new genus and species.